XV Congresso Nazionale di Scienze Planetarie - Brucato, John; Poggiali, Giovanni (Il Colle di Galileo, 2019)
The 15th edition of the Italian National Congress of Planetary Science was held in Florence from the 4th to the 8th of February 2019. During the five-day meeting, the Italian science community of planetology discussed the major discoveries made over the last year and presented the latest results.